An empirical investigation of customer intentions influenced by service quality using the mediation of emotional and cognitive responses. Issue 1 (12th February 2018) - Alsaggaf, Mohammed Ahmad; Althonayan, Abraham
Abstract : Purpose: The purpose of this paper is to investigate the effects of customer perceptions of service quality on electronic word of mouth (eWOM) and switching intentions through cognitive and emotional responses. Design/methodology/approach: The authors have developed a theoretical framework based on behavioural theories to analyse the environmental aspects of relationships that affect customer behavioural intentions. The authors adapted a quantitative methodology along with the positivist philosophical approach to investigate the hypotheses within the theoretical framework. The authors applied a protracted stimuli-organism-response model to highlight the peripheral reliability, responsiveness, tangibility, empathy, assurance, and the impact of the customer's feelings while simultaneously linking the elements to each other. In addition, the authors applied the theory of reasoned action to reflect the marginal elements of subjective norms, attitude, and customers' behavioural intentions. A survey with 601 responses has been used in this study. Findings: In the setting of KSA's mobile telecom industry, the authors confirm that there is a positive effect of customer perceptions of service quality on their eWOM and switching intentions through their cognitive and emotional responses. Originality/value: The framework of this study enhances our understanding of the role of service quality as an environmental influence on an individual's intentions to switch and eWOM. This conceptual framework is essential in evaluating the mediating roles of attitude and emotions in relation to eWOM and intention to switch.